Competência tributária: instituição e arrecadação de tributos no regime federativo - Moraes, Allan (2014)
The present work addresses the tax jurisdiction concept by investigating the principles and limits governing the tax collection activity, in its multiple forms. The constitutional rules that apply to the lawmaking process to create taxes, as well as to ensure the fulfillment of the tax jurisdiction by the political entities, are also discussed. In this sense, the tax jurisdiction is seen as an instrument for the design of the Federative State, a safeguard set forth by the Federal Constitution alongside other rules that guide the tax collection activity, allowing, requiring and prohibiting such conduct